Predicting impact shock magnitude: Which ground reaction force variable should we use? - Greenhalgh, A.; Sinclair, J.; Protheroe, L.; Chockalingam, N. (International Journal of Sports Science and Engineering, 2012)
Peak tibial acceleration (PTA) measured using accelerometers attached to the musculoskeletal system is considered the most effective method of quantifying impact shock magnitude as a result of footstrike during running. Ground Reaction Forces (GRFs) measured using force plates are also widely used to predict PTA. However it is not clear which is the most effective GRF variable to use. This has led to different variables being reported within biomechanics literature. This study aimed to identify which GRF variable is the most suitable for consistent and accurate prediction of impact shock magnitudes. Thirteen participants (10 male and 3 female) took part in this study. Simultaneous tibial accelerations and GRF information were recorded as participants ran at 4.0ms-1+5% over a force platform. The relationship between various GRF parameters including, average vertical loading rates, peak instantaneous vertical loading rates (PIVLR), event times were compared to tibial shock magnitudes using Pearson correlations. The GRF variables analysed identified that the strongest correlation (r=0.469) exists between the PIVLR and the PTA. This study therefore provides evidence that the most effective method of predicting PTA is via the PIVLR. This method does not require identification of a vertical GRF impact peak which is dependent on the individual researcher identifying the peak, and can be identified repeatedly across studies.